Current situation of stakeholders’ characteristics in Chu-mango supply chain - Vo Tuan Truong, Kiet Hong; Sidique, Shaufique Fahmi (WIT Press, 2022)
The paper approached value chain analysis methodology to identify the flow of information and activities between direct and indirect actors at every channel in the supply chain. A simple random technique was used to select 750 sampling observations for the Chu-mango value analysis. The findings indicated 71% of farmers sell their products to collectors, and 18.8% of mango volume is sold to wholesalers. A further 9.2% sell to cooperatives, and a tiny minority (1%) is sold to local retailers. The main role of cooperative and farmer group share farming techniques is to control agrochemical use in the production process of VietGAP, GlobalGAP, traceability code, and providing information on market opportunities to members. Most of collector transacts with farmers and wholesalers are not contractual agreements that are based on a good business relationship and a responsibility to comply with the supply. Wholesaler is pivotal trader in both the output and input partners of actors in the value chain at the regional and national levels. The wholesaler also plays the role of a fresh mango exporter to the Chinese market. The transaction takes place in cash for channel 2, bank transfer for channel 3, and both for channel 4. Processing firms play an essential role in the consumption of Chu-mango grades 3 and 4 of farmers and create value-added products for consumers. However, the percentage of Chumango in exporting enterprises only accounts for a modest proportion of companies’ business operations. Most of fresh mango export enterprises must invest in cool sorting systems, packing factories, and vapor heat treatment factories to ensure the tested fresh fruit before exporting. markets for mango are very promising when Vietnam joins trade agreements such as comprehensive and progressive agreement for the trans-Pacific partnership (CPTPP), the European Union Vietnam free trade agreement (EVFTA), and the Asean economic community (AEC). Most import taxes of partners are zero for Vietnamese mangoes and mango products.